Development of Sos Game Media to Teach Pronunciation in 10th Grade at SMK Mambaul Jadid: English - Izzatul mustaidah; Istina Atul Makrifah; Tyas Alhim Mubarok (Prodi Tadris Bahasa Inggris, 2023)
One of the important skills in English is speaking, because speaking English makes it easier to practice and interact directly. The focus of this research is students' pronunciation of English vocabulary. Based on observations at Mambaul Jadid Vocational School, students’ have trouble in learning English because the module is still LKS-based and the teacher's explanation. Therefore, developing interesting additional media is a must for students not to get bored in learning English. The media game SOS is a game developed by researchers using a specific objective to practice pronunciation in English. Media development uses the RnD Model (Research and Development) and the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The media design is made with a user guide that makes it easy for players. The game media has been validated previously and obtained a final score of 98% in the very valid category. Students as respondents gave their opinion about game media through a questionnaire. The final score of the questionnaire was 89% in the